Free Clean Fill Dirt - Pagel, Caryl (Akron series in poetry., 2022)
Free Clean Fill Dirt, Caryl Pagel's third book of poetry, is a study in disruption, interruption, and ruin, tracing geological and historical palimpsests via caesura, fragmentation, echo, and humor. In these rigorous, formally adventurous poems Pagel calls upon the playful, unsettling sonic sensibilities of writers such as Lorine Niedecker, Russell Atkins, Frank O'Hara, and H. D., as she ties the music of place to personal inquiry: "There is / something in the way / of the thought," the narrator posits: is it sound, desire, violence, or image? Pagel dwells in the anti-ordinary ordinary strata of Midwestern mythologies, emergencies, landscapes, and crises. Using a blend of ecopoetic, visual, and archival modes, Free Clean Fill Dirt is a collection of poems making intimacy of deep time and vanitas of vision.